(untitled) (Journal of Hama University, 2024)
Aim of The Study: This study aims to evaluate the effect of bleaching in dental clinics on the shear-resistant bond strength of both ceramic and metal orthodontic brackets bonded with composite resin immediately after bleaching and to compare their SBSs after preparing the enamel surface with phosphorous acid or laser, in addition to measuring the adhesive residue index (ARI) on the brackets. After a link failure. Materials and Methods: The sample consisted of 80 upper premolars, which were randomly divided into eight groups with ten teeth in each group, as follows: Groups (1-3-5-7) were not subjected to bleaching and then bonding immediately. Groups (2-4-6-8) were subject to bleaching and then bonding after 24 hours after the bleaching procedure, the metal brackets were adhered to the composite resin in groups (1-2-5-6) and the ceramic brackets in groups (3-4-7-8), and then a shear bond strength (SBS) Shear Bond test was completed. Strength of the samples using a mechanical testing device, then the Adhesive Remnant Index (ARI) was checked after removing the brackets. The data was analyzed statistically. Results: There are significant differences of P < 0.05 (SBS) between the experimental groups, as the average bond strength in the current study was. The third group, which was not subjected to bleaching and laser etching and then glued the ceramic brackets, had the highest bond strength value, as the average shear-resistant bond strength was 7.85±1.18 MPa.With an evaluation of the failure mode for the variable ARI at the port – adhesive There are no statistically significant differences in the average amount of adhesive remaining on the bracket when comparing the eight groups Conclusion: The procedure of bonding ceramic brackets with composite resin directly after applying bleaching in the clinic gives a clinically acceptable bond strength. Using ceramic brackets instead of metal brackets after bleaching gives greater bond strength Applying laser etching after bleaching gives greater bond strength than using acid